Réponses

2014-02-23T00:28:18+01:00
5x + 3 - (7 - 6x) + ( - 4x - 8) = 5x + 3 -7 +6x -4x -8
                                              = 7x -12
 DEVELOPPER ET REDUIRE :
3x(6 - 2x) + x ² - 12 = 18x -6x² +x² -12    
                                = -5x²  +18x -12     
(X + 4)(X + 1) - 4 (1 -5X) = x² +x +4x +4 - 4 +20x
                                        = x² +25x
                                        = x( x+25)  
RESOUDRE:
 x/3 = 4/7      
7x= 4*3
7x = 12
x = 12/7              
2014-02-23T01:14:29+01:00
A = 5x + 3 - (7 - 6x) + ( - 4x - 8)
A = 5x + 3 -7 +6x -4x -8
= 7x -12

Developper et reduire :

A = 3x(6 - 2x) + x ² - 12 
A = 18x -6x² +x² -12 

A = -5x²  +18x -12    

A = (X + 4)(X + 1) - 4 (1 -5X) 
A = x² +x +4x +4 - 4 +20x

A = x² + 25x
                                     
RESOUDRE:

 x/3 = 4/7      
7x= 4*3
7x = 12

x = 12/7